The Effect of Nano-Encapsulation Phaleria macrocarpa Fruits Extract in Drinking Water on the Digestive Tract and Carcass Characteristic of Broiler Chickens - Zuprizal Zuprizal; Niati Ningsih; Taufik Ahmad Zulfian (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
The present study was to evaluate the effects of nano-encapsulated Phaleria macrocarpa fruit extract (NEPM) in drinking water on the digestive organs and carcass characteristic of broiler chickens. A total number of two hundred male broiler chicks were randomly divided into five treatments with four replicates, each replicate contained ten chickens. Broiler chickens have received a basal diet supplemented with or without experimental treatments. Five experimental treatments were: control diet (T0; negative control), diet with tetracycline (T1; positive control), diet with 2.5% of Phaleria macrocarpa fruits extract (T2), diet with 2.5% NEPM (T3), and diet with 5.0% NEPM (T4). The diets were based on yellow corn and soybean meal and contained 20.44% crude protein, 2,917.47 kcal/kg metabolizable energy, 0.84% Calcium, and 0.51% available Phosphorus. On the 35th day, one bird from each replicate pen was slaughtered. Carcass characteristics and weights of digestive organs were measured. Data were statistically analyzed using ANOVA in a completely randomized design. The orthogonal contrast test was used to separate the mean when the P-value was less than 5%. Results showed that the use of nano-encapsulated Phaleria macrocarpa fruits extracts up to 5.0% in the diet did not give any significant effect on the carcass, digestive organs, heart and liver weights of broiler chickens. It can be concluded that the supplementation of Phaleria macrocarpa fruits extracts whether nano-encapsulated or not, did not affect carcass weight, weights of digestive organs and weights of the heart and liver of broiler chickens.